Language of Instruction in Higher Education: South Africa and Spain - Liu, Xinyan (Romance eReview, 2019)
The author offers a compelling look at the intersection between language and identity by studying the language of instruction used in the multilingual countries South Africa and Spain. Language is in many ways, a central force for human society, as we depend on language to organize, express, create and interact. Language is a vehicle of knowledge, thus a central piece to academia. Higher education used to be closely tied to a small elite class in society. People who spoke languages that did not have standardized written forms or active coding of knowledge production were automatically barred from higher education. Since massification of higher education started taking place worldwide, the rapid expansion of higher education institutions is encountering many challenges. Among them, language of instruction (LoI), particularly in multilingual societies, becomes a key component in issues of equity and access, conflicting identities, and forces of globalization and internationalization. Equity and access are universal issues in higher education in this unequal world. Home languages are often not represented in the public domain. This paper presents and discusses two countries on two continents: South Africa and Spain. While the two countries certainly do not represent the larger African and European context, they may reflect some general trends of their respective continents. The following sections will focus on their respective sociolinguistics histories, higher education systems and policy frameworks. We will end with reflections on the implementations of language policies in both contexts and how we may move forward under the blueprint of internationalization.